Oxygen Nonstoichiometry and Cathodic Property of Ce0.6Mn0.3Fe0.1O2-δ for High Temperature Steam Electrolysis Cell Using LaGaO3-Based Oxide Electrolyte. (2nd June 2015) - Hosoi, Kohei; Sakai, Takaaki; Ida, Shintaro; Ishihara, Tatsumi
Abstract : Steam electrolysis was studied by using a new oxide cathode of Ce0.6 Mn0.3 Fe0.1 O2- d (CMF). It found that this cathode showed almost same performance compared with a conventional Ni-based cathode without H2 flow and H2 generation rate obeyed the Faraday's law at 900-700°C. The result of XRD measurement after operation, CMF phase were hardly changed after the steam electrolysis. A long-termed durability test was operated, and it revealed that CMF cathode showed the good stability over 90 h at 800 °C. The impedance spectra were measured under applied DC bias potentials. It revealed that polarization resistance and ohmic resistance were decreased with increasing DC bias potential. This decreasing of ohmic resistance was related to the increasing in electronic conductivity of CMF. CMF was n-type semiconductor and then electronic conductivity of CMF increased with decreasing of oxygen partial pressure.